Molecular Structure and Phylogenetic Analyses of the Complete Chloroplast Genomes of Three Medicinal Plants Conioselinum vaginatum, Ligusticum sinense, and Ligusticum jeholense - Wei, Xue-Ping; Zhang, Xiao-Yi; Dong, Yu-Qing; Cheng, Ji-Long; Bai, Yun-Jun; Liu, Jiu-Shi; Qi, Yao-Dong; Zhang, Ben-Gang; Liu, Hai-Tao (Frontiers in Plant Science, 2022)
Most plants of Ligusticum have an important medicinal and economic value with a long history, Ligusticum sinense and L. jeholense (“Gaoben”) has long been used in traditional Chinese medicine for the treatment of carminative, dispelling cold, dehumidification, and analgesia. While in the market Conioselinum vaginatum (Xinjiang Gaoben) was substitution as Gaoben, and occupies a higher market share. These three Gaoben-related medicinal materials are similar in morphology, and are difficult to distinguish from each other by the commonly used DNA barcodes. The chloroplast genome has been widely used for molecular markers, evolutionary biology, and barcoding identification. In this study, the complete chloroplast genome sequences of L. sinense, L. jeholense and C. vaginatum were reported. The results showed that the complete chloroplast genomes of these three species have typical quadripartite structures, which are comprised of circular 148664,148539 and 148497 bp long. A total of 114 genes were identified, including 81 protein-coding genes (PCGs), 29 tRNA genes and four rRNA genes. Our study indicated that highly variable region ycf2-trnL and accD-ycf4 that can be used as specific DNA barcodes to distinguish and identify C. vaginatum, L. sinense and L. jeholense. In addition, phylogenetic study showed that C. vaginatum nested in Ligusticum and as a sister group of L. sinense and L. jeholense, which suggested these two genera are both in need of revision. This study offer valuable information for future research in the identification of Gaoben-related medicinal materials and will benefit further phylogenetic study of Apiaceae.